Assessment Of Heavy Metals Concentration and Pollution Indices Of Surface Water In Enerhen River, Warri South LGA, Delta State, Nigeria - A. O. Egai; M. Paaru (Journal of Applied Sciences and Environmental Management, 2025)
The objective of this paper is to assess heavy metal concentrations and pollution indices of surface water in Enerhen River, Warri South, Delta State, Nigeria using appropriate standard method.   Data obtained show that the result indicated the concentration of Zinc 0.065mg/l - 0.190mg/l, Pb (0.003mg/l -0.142mg/l), Cu (0.081mg/l - 0.213mg/l), Cd (0.02mg/l - 0.282mg/l, Cr (0.041mg/l - 0.171mg/l), Fe (0.162mg/l - 0.278mg/l) and Ni (0.104mg/l - 0.762mg/l)  comparison with WHO 2012 permissible limit the probed water sample falls within the allowable concentration of the standard except the  concentration of lead (Pb) in SW1, SW2, SW4 and SW5 which is a  concern because it exceeded the allowable limit, lead is considered toxic to human at higher concentrations . The computed indices for the maximum admissible concentration upper permissible values buttress as follows Zn 0.3MAC, Pb 0.01MAC, Cu 2MAC, Cd 0.01MAC, Cr 0.05MAC, Fe, 0.3MAC and Ni 0.02MAC. Also, the interpretation of the assessment of pollution indices with connotations as heavy metal pollution indices (HPI), Heavy metal evaluation index (HEI) and Degree of contamination as CD. The values from the analysed sample locations are as follows SS1 for HPI value gives (3869.928), HEI (103.0056)  and  CD ( 96.00583). For SS2 HPI value gives as (6157.674), HEI (100.4356) and CD (93.4353).  SS3 HPI (5394.674), HEI (102.2192) and CD (95.21933), SS4 HPI (507.0053), HEI (20.39265), CD (13.39267) and SS5 HPI (568.5303), HEI (25.9153) and CD (18.9154) .The HPI indicated values >150 which expresses high concentration of heavy metal pollution. Similarly the HEI also indicated values > 20 which again buttress high heavy metal evaluation index and the degree of contamination also gives values > 3 which indicate a   higher level of contamination in the samples. The River water is recommended for treatment before use due to the higher concentration of Nickel, Pb and Cadmium especially lead (Pb) which is deleterious to human health.